Factors Affecting Evaluation Influence in the Public Sector of Cam Lo District, Vietnam - Ha, Tri Minh; Nguyen, Phuc Van (International Review of Management and Marketing, 2017)
This study seeks to answer what factors may affect evaluation influence in the public sector of Cam Lo District in Vietnam. Exploratory factor analysis (EFA) was used to extract factors that may affect evaluation influence. This procedure returned five factors, including involvement of evaluation partners, evaluation capacity, evaluation plans and methods, generation of evaluation report, and dissemination evaluation findings. Confirmatory factor analysis (CFA) was used to verify whether the measured variables that were written to reflect the identified factors are reliable and valid. Path analysis was then conducted to investigate the relationships between the factors identified and evaluation influence. Survey data collected from 275 staff of in 2015 Cam Lo District highlight that two out of the five factors (i.e., evaluation capacity along with evaluation plans and methods) identified on the basis of the proposed conceptual framework have a statistically significant effect on evaluation influence. Keywords: Evaluation influence, evaluation use, research on evaluation, theory of evaluation influence, Vietnam. JEL Classifications: J24, H70